Seaside Operations Planning in Container Terminals - Meisel, Frank (Contributions to Management Science,, 2009)
Tremendous annual growth rates of container volumes transhipped worldwide reflect an increasing demand of service capacity faced by container terminals. In spite of high utilization, terminals have to provide fast service processes to vessel operators. This book addresses the related seaside operations planning problems by investigating berth allocation, quay crane assignment and quay crane scheduling. It provides extensive literature surveys, new models and new algorithms for these optimization problems. In contrast to other research in the field, this book strives for an integrated solution of the planning tasks, respecting existing interrelations between the utilization of quay space and quay cranes. For this purpose, the studies in this book are aligned to a new integration concept for seaside operations planning in container terminals. The planning methodology supports a highly productive utilization of quay space and quay cranes leading to reliable and fast service processes of vessels.